Between market and mayor: talent management in Chinese private firms and the role of local governments. (27th May 2022) - Zhao, Chenhui; Cooke, Fang Lee; Chen, Lanlan; Xiao, Qijie
Abstract : There is now a substantial body of literature on talent management (TM). However, this relatively young field of research has been primarily segmented into macro‐, meso‐ and, mostly, micro‐level studies with little cross‐level interrogation. Our case study, involving 42 interviews and four focus groups with local government leaders, company managers and talent, contributes to the conceptualization of the role of local governments as important stakeholders in the process of developing a TM system in leading private firms in China to help achieve regional economic development goals. We develop a three‐level analytical framework to map out how the local government legitimizes its power and mobilizes resources to shape the TM system of the two leading private firms in our study. By assessing the role of the local government in the construction of the talent network and TM strategy, policy and practice at firm level, we reveal how the network is shaped by the state as the lead actor through a set of strategic interventions to align and achieve government and business goals through a government‐business relations perspective.